Foldamers. Issue 17 (6th June 2013) - Tomasini, Claudia; Huc, Ivan; Aitken, David J.; Fülöp, Ferenc
Abstract: Our Guest Editors introduce this special issue on Foldamers. "This collection of publications gives a flavour of how the foldamers research area is continuously growing and expanding and we trust that it will be informative and stimulating for the organic chemistry community." Abstract : Our Guest Editors introduce this special issue on Foldamers. "This collection of publications gives a flavour of how the foldamers research area is continuously growing and expanding and we trust that it will be informative and stimulating for the organic chemistry community."